Nurses’ Experience of Ethical Dilemma at the End-Of-Life Care in the Intensive Care Unit - Arianto, Albertus Budi; Trisyani, Yanny; Emaliyawati, Etika (Jurnal Keperawatan Soedirman, 2022)
One of the aims of the care service in the Intensive Care Unit (ICU) is to prepare patients in end-of-life conditions to die in a dignified manner. This can be challenging due to decision-making problems and result in a dilemma. Therefore, this study explores the ethical dilemmas experienced by nurses that provide end-of-life care in the ICU. The qualitative phenomenological methodology was used to describe the ethical dilemmas nurses face during these conditions. The data were collected through in-depth interviews and were analyzed using Colaizzi. Purposive sampling was used to select a total of eight participants, i.e., ICU nurses, who have treated end-of-life patients. Four themes were obtained from this study, namely, “the dilemma between the family’s decisions and continuing care”, “patient’s life expectancy and the family’s hope”, “DNR decisions and the nurse’s confidence”, and “the family’s understanding of the information provided”. This study recommends that the assessment of end-of-life status in critical care areas, especially the ICU, should be conducted as soon as possible to have a clearer purpose for the care provided.